ANALISIS KELAS KEMAMPUAN KELOMPOK TANI PADI SAWAH BERDASARKAN FUNGSI KELEMBAGAAN DI KELURAHAN RANOMEETO KECAMATAN RANOMEETO KABUPATEN KONAWE SELATAN - Femi Sarlina; La Nalefo; Salahuddin Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
Farmers’ groups are farmer institutions that play a crucial role in enhancing members’ capacity through learning, cooperation, and agricultural business development. A farmers’ group’s ability to carry out its institutional functions serves as the basis for determining its capability class, which reflects the level of development of the farmer organization. This study aims to analyze the capability classes of irrigated rice farmers’ groups based on their institutional functions in Ranomeeto Village, Ranomeeto Subdistrict, South Konawe Regency. This study employs a quantitative approach using a survey method. The study population consists of 106 farmers who are members of six active farmers’ groups under the Sri Kembang Farmers’ Association (Gapoktan). The sample of 51 respondents was determined using the Slovin formula and selected through proportional random sampling. Data were collected through interviews using a questionnaire, literature review, and documentation, and were then analyzed descriptively and quantitatively using scores and percentages. The results indicate that the farmers’ groups’ capabilities vary across the institutional functions analyzed. Relatively high capabilities were observed in the areas of building cooperation with other parties, utilizing facilities and infrastructure, and taking corrective actions to address group issues. Conversely, areas requiring improvement include active member participation, cooperation in carrying out activities, and the recording and documentation of group activities. Overall, the farmer groups have demonstrated fairly good capabilities in carrying out their institutional functions, particularly in operational aspects and the development of institutional networks. However, strengthening organizational capacity, group administration, and member engagement is still necessary to improve the effectiveness of farmer group management. The findings of this study provide important information for agricultural extension workers and local governments in formulating strategies for the sustainable institutional strengthening of farmers.